A reactive oxygen species-generating, cyclooxygenase-2 inhibiting, cancer stem cell-potent tetranuclear copper(ii) cluster. Issue 38 (21st September 2017) - Lu, C.; Laws, K.; Eskandari, A.; Suntharalingam, K.
Abstract : Tetranuclear copper(ii ) complexes containing multiple diclofenac and Schiff base moieties, 1–4, are shown to kill bulk cancer cells and cancer stem cells (CSCs) with low micromolar potency. Abstract : Tetranuclear copper(ii ) complexes containing multiple diclofenac and Schiff base moieties, 1–4, are shown to kill bulk cancer cells and cancer stem cells (CSCs) with low micromolar potency. The most effective complex, 1, elicits its cytotoxic effect by elevating the intracellular reactive oxygen species (ROS) levels and inhibiting cyclooxygenase-2 (COX-2) expression.